Telechelic polyethylene, poly(ethylene-co-vinyl acetate) and triblock copolymers based on ethylene and vinyl acetate by iodine transfer polymerization. Issue 17 (22nd March 2022) - Baffie, Florian; Lansalot, Muriel; Monteil, Vincent; D'Agosto, Franck
Abstract : Difunctional iodo chain transfer agents (CTAs) were successfully employed in the iodine transfer polymerization (ITP) of ethylene and its copolymerization with vinyl acetate to synthesize telechelic (co)polymers and triblock copolymers. Abstract : Various iodo functionalized chain transfer agents (CTAs) were successfully employed in the iodine transfer polymerization (ITP) of ethylene conducted at 80 bars at 70 °C in dimethylcarbonate. Comparative studies performed on I–C6 F12 –I, C6 F13 –I, C6 F12 (CH2 )2 –I and C5 H10 –I mediated ITPs revealed that when I–C6 F12 –I was used as CTA the very first ethylene additions resulted in the formation of diiodo oligomeric compounds with various chain transfer activities. This however did not impede a good control of the polymerization that was rapidly installed. This allows the formation of well-defined telechelic polyethylene (I–PE–I) and poly(ethylene- co -vinyl acetate) (I–EVA–I) by ITP. I–EVA–I telechelic copolymers were further used as macromolecular CTAs in chain extension experiments in the presence of ethylene to lead to PE- b -EVA- b -PE triblock copolymers with different content of VAc (27 and 64 mol%) in the central EVA block.